Manajemen Hipotermia pada Cedera Kepala - Tri Wahyuni Ismoyowati; Ceacilia Nika Candra Kusuma; Mega Agape Timisela (FORIKES, 2020)
Head injury is a serious health problem. Mortality and morbidity in patients with head injuries are mostly due to increased intra-cranial pressure (ICP). This is increases ischemia and brain herniation. This paper discusses about hypothermia management in head injury patients. This paper discusses about hypothermia management in head injury patients. The search was performed using the following keywords: